Delayed health care seeking is high among patients presenting with sexually transmitted infections in HIV hotspot areas, Gambella town, Ethiopia - Tsadik M (HIV/AIDS : Research and Palliative Care, 2019)
Mache Tsadik,1 Lul Lam,2 Zinabu Hadush11School of Public Health, College of Health Science, Mekelle University, Tigray, Ethiopia; 2Department of Disease Prevention and Control, Gambella Regional Health Bureau, EthiopiaCorrespondence: Mache TsadikSchool of Public Health, College of Health Science, Mekelle University, Tigray, EthiopiaTel +251 91 474 3841Email adhana2008@gmail.comBackground: Delayed health care seeking is one of the major impediments to successfully prevent and control sexually transmitted infections (STIs) including HIV. Gambella is one of the HIV hot spot areas and the most HIV prevalent region in the country. Considering the empirical knowledge of the link between STIs and HIV, gathering information on health-seeking behavior and the associated factors among STI patients is helpful to design interventions that enhance early seeking and treatment adherence.Methodology: A facility-based cross-sectional study was employed to collect data from 424 STI patients from February 15 to April 15, 2017, using a face-to-face interview. A consecutive sampling method was used until the allocated sample for each facility was fulfilled. A multivariate logistic regression analysis was used to identify factors associated with health-seeking behavior.Results: The proportion of delayed health care seeking among patients treated for STIs was 56.8%. Knowledge, number of sexual partners, and perception variables were found significantly associated with early seeking behavior in multivariate logistic regression: patients who had better knowledge of STIs (AOR =1.74, 95% CI =1.10, 2.73), had single sexual partner (AOR =1.83, 95% CI =1.19, 2.78), those who perceived stigma for STIs (AOR =0.52, 95% CI =0.34, 0.79), and perceived severity of STIs (AOR =1.97, 95% CI =1.18, 3.29).Conclusion: This study reported a high proportion of delayed health care seeking. This may challenge the prevention and control effort and alarms the potential threat to the spread of STI/HIV in the region. Provision of intensive health education is crucial to improve awareness and to avoid risk behaviors and negative perceptions.Keywords: health, seeking, behavior, sexually, transmitted, infection, Gambella